Measurement of the Z gamma -> nu(nu)over-bar gamma production cross section in pp collisions at root s=8 TeV and limits on anomalous ZZ gamma and Z gamma gamma trilinear gauge boson couplings - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
An inclusive measurement of the Z gamma -> nu(nu) over bar gamma production cross section in pp collisions at root s = 8 TeV is presented, using data corresponding to an integrated luminosity of 19.6fb(-1) collected with the CMS detector at the LHC. This measurement is based on the observation of events with large missing energy and with a single photon with transverse momentum above 145 GeV and absolute pseudorapidity in the range vertical bar eta vertical bar < 1.44. The measured Z gamma -> nu<(nu)over bar>gamma production cross section, 52.7 +/- 2.1(stat) +/- 6.4(syst) +/- 1.4(lumi) fb, agrees well with the standard model prediction of 50.0(-2.2)(+2.4) fb. A study of the photon transverse momentum spectrum yields the most stringent limits to date on the anomalous ZZ gamma and Z gamma gamma trilinear gauge boson couplings. (C) 2016 The Author(s). Published by Elsevier B.V.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Measurement of the Z gamma -> nu(nu)over-bar gamma production cross section in pp collisions at root s=8 TeV and limits on anomalous ZZ gamma and Z gamma gamma trilinear gauge boson couplings. Physics Letters B, 760, 448-468. doi:10.1016/j.physletb.2016.06.080
Keywords: Photon; Met; Hadron Colliders; Sector; Tevatron; Astronomy & Astrophysics